Determination of Cr(III) and Cr(VI) Concentrations of the Jiu and Olt Rivers of Romania - BARBU, CRISTINA; POPESCU, ALEXANDRU; PREDA, ANISOARA; SELISTEANU, DAN; STANCA, DAIANA; BRANESCU, VALENTIN (Asian Journal of Chemistry, 2010)
This paper presents a comparative study of Cr(III) and Cr(VI) distribution on Jiu and Olt rivers. The concentration of Cr(III) and Cr(VI) in Jiu river were determined using inductively coupled plasma mass spectrometry while for Olt river by atomic absorption spectrometry.